Prevalence of Gestational Hypertension and Pregnancy Outcome - Bhat AV; Kharde SN (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction Hypertension during pregnancy is considered as one the high risk as it is one of the cause for maternal and neonatal mortality and morbidity. Aims: This study is aimed to find the prevalence of gestational hypertension and to understand the pregnancy outcome. Settings and Design: Study conducted at tertiary care hospital and descriptive research design was used for the study Methods and Material: Sample size was 366 women with gestational hypertension were included. Data was collected by using investigator prepared self-administered questionnaire Statistical analysis used: inferential statistics analytical methods Results: Results revealed that prevalence of gestational hypertension 9.8%. Maternal outcome 53% delivered at 34 to 38 weeks, mode of delivery (52.5%) were delivered by C-section, 56.3% women were induced, 97.3% were singleton pregnancy, About the gender of new-born 51.9% were male, 67.2% were born with Normal (>2500g) weight, NICU admission 20.5% and reason for NICU admission was prematurity. Conclusions: The knowledge of risk factors for gestational hypertension in pregnancy may give tracks for prevention in this population.